(untitled) (Journal of Plant Disease Sciences, 2018)
Molecular characterization of MPKV biofertilzer was focused to identify the molecular diversity among different bacterial species by employing DNA fingerprinting technique. Ten RAPD primers of OPB series viz., RBa-01, RBa-02, RBa- 03, RBa-04, RBa-05, RBa-06, RBa-07, RBa-08, RBa-09 and RBa-10 were used for RAPD analysis. Out of these, RBa- 01, RBa-04 and RBa-06 yielded good and different banding pattern. The size range of the bands amplified with selected ten random primers was found in between 5500bp to 250bp when compared with DNA molecular weight marker of 1kb. On the basis of variation of size number and intensity of bands, Rhizobium species were grouped into two groups; Group I contains Bradyrhizobium japonicum, Rhizobium loti and Rhizobium spp. and Group II contains Rhizobium meliloti, Rhizobium leguminasorum which depicts the diversity between them. This study demonstrates that the RAPD markers are useful in assessing diversity at genetic level rather than morphological markers which are subjected to environmental fluctuations.